Changes in neuromuscular status across a season of professional men's ice hockey - Gannon, E. A.; Higham, D. G.; Gardner, B. W.; Nan, N.; Zhao, J.; Bisson, L. J. (The Journal of Strength and Conditioning Research, 2021)
To quantify changes in neuromuscular function over a full professional men's ice hockey season, 27 players (n = 18 forwards and 9 defensemen) performed 3 countermovement jumps (CMJ) each week over 30 sessions separated into 4 phases: preseason, early-season, midseason, and late-season. Outcome variables represented jump performance (jump height), kinematics (mean velocity and peak velocity), and movement strategy (countermovement depth). Mixed models characterized relationships between positional group, season phase, and CMJ outcomes. Statistical significance was set at p = 0.05. Concentric peak velocity (p = 0.02), jump height (p = 0.001), and countermovement depth (p < 0.001) displayed a significant reduction across the season. Peak velocity was lower during the early-season than the preseason (-0.10 ± 0.06 m·s-1, mean change ± 95% confidence limit, p = 0.05). Countermovement depth was reduced during the early-season (-0.06 ± 0.03 m, p = 0.02), midseason (-0.10 ± 0.04 m, p = 0.002), and late-season (-0.15 ± 0.04 m, p < 0.001) relative to the preseason. Reductions in CMJ variables from preseason to in-season ranged from trivial to large. Changes in countermovement depth differed for forwards and defensemen by the season phase (p = 0.04). A professional ice hockey season decreases CMJ performance, with the effects of fatigue most prominent during the late-season phase. Countermovement depth was most sensitive to fatigue and differentiated positional-group responses. Frequent CMJ testing is useful for identifying the neuromuscular status of team-sport athletes relative to season-specific phases. Fatigue monitoring should incorporate movement-strategy variables alongside traditional measures of performance and kinematics.